2021
DOI: 10.1063/5.0048444
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric P(VDF-TrFE) film inkjet printed on silicon for high-frequency ultrasound applications

Abstract: We investigated the innovative processing of poly(vinylidene fluoride-trifluoroethylene) P(VDFx-TrFE1-x) (x = 83 mol. %) by inkjet printing to deliver uniform and thickness-controlled layers on silicon substrates. Here, we provide detailed processing steps and optimize film deposition conditions. The thickness coupling factor for a P(VDF-TrFE) film around 11 μm thick was 22%, demonstrating good electromechanical performance after poling. These multilayer structures were specifically for high-frequency, single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The highest age of the patients was 68 years old, and the lowest was 22 years old, with an average of (41:31 ± 3:34) years old. Comparing the clinical data of the two groups, there was no significant statistical significance (P > 0:05), and the data were highly comparable [12]. Inclusion criteria: (1) The experimental group was confirmed as subacute thyroiditis by pathological diagnosis.…”
Section: Experimental Analysismentioning
confidence: 99%
“…The highest age of the patients was 68 years old, and the lowest was 22 years old, with an average of (41:31 ± 3:34) years old. Comparing the clinical data of the two groups, there was no significant statistical significance (P > 0:05), and the data were highly comparable [12]. Inclusion criteria: (1) The experimental group was confirmed as subacute thyroiditis by pathological diagnosis.…”
Section: Experimental Analysismentioning
confidence: 99%
“…The inkjet-printed piezoelectric P(VDF-TrFE) film on silicon was investigated by Banquart et al and electro-acoustic responses of multi-layer structures, which are specifically designed for high-frequency, single-element ultrasonic transducer applications, were measured in water. The results showed that maximal frequency was centered at 33.2 MHz and had a fine axial resolution at 22 µm, corresponding to a fractional bandwidth at − 6 dB of 100% [277]. This can be used in multi-element transducers for high-frequency imaging applications.…”
Section: Functional Membranementioning
confidence: 90%
“…Inks and processes for IJP EAP have been developed for P(VDF-TrFE) in [21], and for both P(VDF-TrFE) and P(VDF-TrFE-CTFE) in [22], whereas the latter study further used sputtering to deposit Au electrodes to produce force sensors. Banquart et al reported IJP a P(VDF-TrFE) layer on a silicon substrate and sputter-coating the top electrode to form ultrasound transducers [23], and Abdolmaleki et al combined IJP of P(VDF-TrFE)-AGO nanocomposites with painting Ag electrodes to form biomedical monitoring sensors [24]. P(VDF-TrFE)-based transducers with IJP'ed Ag electrodes were reported by Alique et al [25], and P(VDF-TrFE-CTFE)-based actuators with IJP'ed carbon black electrodes were reported in [26,27], whereas the EAP layers in these studies were respectively screen-printed and spincoated.…”
Section: Introductionmentioning
confidence: 99%